Future Climate Scenarios for Northern Baffin Bay and the Pikialasorsuaq (North Water Polynya) Region. Issue 2 (15th March 2022) - Buchart, Liam; Castro de la Guardia, Laura; Xu, Yiran; Ridenour, Natasha; Marson, Juliana M.; Deschepper, Inge; Hamilton, Andrew K.; Grivault, Nathan; Myers, Paul G.
ABSTRACT: Northern Baffin Bay is distinct due to the presence of the North Water Polynya, a region referred to as "Pikialasorsuaq" by Inuit in Greenland and "Sarvarjuaq" by Inuit in Canada. Surrounding communities rely on the polynya as hunting and shipping grounds for much of the year due to its lower sea ice concentration and high primary productivity; however, Arctic warming threatens the dynamics of the region by altering the sea ice cycle, oceanic heat content and freshwater input. The aim of this study is to examine the future of northern Baffin Bay and Pikialasorsuaq under various climate warming scenarios using the Nucleus for Modelling of the Ocean (NEMO) engine, coupled to the Louvain-la-Neuve (LIM2) sea ice model. Five experiments were run on a 1 / 4 ∘ resolution Arctic and Northern Hemispheric Atlantic (ANHA4) configuration over the period 1981–2070 forced by a range of global climate models. By 2070 there is a significant decrease in sea ice thickness and concentration, with an overall warming and salinity increase in the upper 500 m of the water column. Increased freshwater input from melting Greenland glaciers results in a more muted salinity increase in the top 50 m, while deeper waters are impacted by increased penetration of warm, saline Atlantic Water into Baffin Bay through Davis Strait. These physical changes impact the formation of the polynya in the future. The polynya is expected to continue to form on the eastern side near Greenland through mixing of warm Atlantic Waters to the surface, while the western side near Ellesmere Island has an increased ice area flux through Nares Strait and increased stratification. Additionally, there is a shallowing of mixed layer depth and increase in density stratification under the greatest warming scenarios. Implications to biogeochemical properties include a 0.5% decrease in total alkalinity, a 3.4% decreased in dissolved oxygen concentration but no net change in annual phytoplankton primary production. However, there are large changes in the phytoplankton bloom dynamics, including a 50% decrease in the autumn bloom and a 20-day advance in the spring bloom. Overall, our study suggests significant oceanographic changes which could lead to a loss of the recurrent polynya in its historical state, and shifts in primary production which could have, as yet uncertain, consequences for the food web and higher trophic levels.